Strategic Litigation in EU Law: Who does it Empower? - Cebulak, Pola; Morvillo, Marta; Salomon, Stefan (German law journal, 2024)
Strategic litigation is a form of legal mobilization, where actors bring cases before judges not only to win in court, but also to pursue broader political, social or economic ends. Various actors can use the law strategically – big corporations, specialized non-governmental organizations or individual academics. The ends can range from resisting market regulation or a political advocacy campaign to simply “testing the law”. The results of strategic litigation maintain or change power relations in society, economy or politics. This article provides an analytical framework for the Special Issue on Strategic Litigation in EU Law. This framework can be used to study strategic litigation mobilizing EU law. A contextual and normatively open definition of strategic litigation, recognizes that strategic litigation as a practice operates within specific social, institutional, and economic contexts while accommodating a spectrum of agendas from progressive to conservative. The framework encompasses three dimensions: the actors involved, the unique legal structures of EU law, and its effects—both in terms of strictly legal outcomes and of broader socio-political consequences. Ultimately, this framework aims to illuminate the dynamics of (dis)empowerment characterizing strategic litigation, paving the way for a comprehensive exploration of its implications within the EU legal landscape.